Peningkatan Kemampuan Membaca Permulaan Melalui Metode Bermain Balok (Scrabble) pada Murid Tunagrahita - Meidina, Tatiana; Sulasminah, Dwiyatmi (JOEAI (Journal of Education and Instruction), 2022)
The purpose of this study was to determine the effect of playing with blocks (scrabble) on early reading skills in elementary grade II mild mentally retarded students at SLB D YPAC Makassar. This research is a single Subject Research. The population of this study were students with mild mental retardation in class II SLB D YPAC Makassar, totaling 3 people. Data collection techniques using Test Techniques and Observation Techniques, the data obtained were processed descriptively. The results showed that the initial reading ability in elementary grade II mild mentally retarded students at SLB D YPAC Makassar at Baseline 1 (A-1) all mild mentally retarded students were still below the minimum completeness criteria set, namely a score of 60. At the time of intervention (B) there has been a student with mild mental retardation whose score is above the specified minimum completeness criteria. Meanwhile, after a time lag of 2 weeks, the result of Baseline 2 (A-2) was only a mentally retarded student whose reading ability was still below the specified minimum completeness criteria and still required more intensive attention. In conclusion, the Block Playing Method (Scrabble) can significantly improve the Beginning Reading Ability of the Elementary Grade II Mild Mentally Impaired Students at SLB D YPAC Makassar. Keywords: Beginning Reading Ability, Block Playing Method, Mentally Impaired